Islamiyat 2058 paper2 - Bilal, Younus (Read & write Pakistan, 2019)
"Islamiyat 2058 Paper 2" focuses on the critical analysis and understanding of Islamic beliefs, practices, and history, offering students an opportunity to demonstrate their knowledge and critical thinking in the Cambridge O-Level examination.